1967
DOI: 10.2307/2786437
|View full text |Cite
|
Sign up to set email alerts
|

Observer-Model Similarity in the Contagion of Aggression

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Sun,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1971
1971
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Most specific to the present thrust, future research needs to focus on the ways social influence principles might operate differently when an individual's preexposure public and private positions do not match. Again, the disinhibitory contagion of aggression has been found to be stronger and more likely when the model is dissimilar to the target (Baron & Kepner, 1970;Goethals & Perlstein, 1978;Wheeler & Levine, 1967) rather than similar, as is the case with conformity. However, it is not known with any degree of certainty whether this dissimilarity effect is (a) a general feature of social influence when public and private attitudes are discrepant, (b) a general feature of disinhibitory contagion, or (c) simply an idiosyncrasy of the disinhibition of aggression.…”
Section: Limitationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Most specific to the present thrust, future research needs to focus on the ways social influence principles might operate differently when an individual's preexposure public and private positions do not match. Again, the disinhibitory contagion of aggression has been found to be stronger and more likely when the model is dissimilar to the target (Baron & Kepner, 1970;Goethals & Perlstein, 1978;Wheeler & Levine, 1967) rather than similar, as is the case with conformity. However, it is not known with any degree of certainty whether this dissimilarity effect is (a) a general feature of social influence when public and private attitudes are discrepant, (b) a general feature of disinhibitory contagion, or (c) simply an idiosyncrasy of the disinhibition of aggression.…”
Section: Limitationsmentioning
confidence: 93%
“…Disinhibitory contagion has been demonstrated and examined in numerous empirical studies (e.g., R, A. Baron & Kepner, 1970;Goethals & Perlstein, 1978;Levy, 1992;Russell, Wilson, & Jenkins, 1976;Wheeler & Caggiula, 1966;Wheeler & Levine, 1967;Wheeler & Smith, 1967). The Levy (1992) and Wheeler and Caggiula (1966) studies are described in some detail below.…”
Section: Disinhibitory Contagionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goethals (1972) found that dissimilar agreers are as influential, or more so, than similar agreers if they have the same information about the entity being judged. Wheeler and Levine (1967) have shown that a dissimilar model is more effective in inducing the contagion of aggression.…”
mentioning
confidence: 99%
“…One function of the morally justified violence which the subject then observed may have been the disinhibition of aggressive acts which he was motivated to commit. Such an interpretation is also suggested by studies conducted by Wheeler and his associates (Wheeler and Caggiula, 1966;Wheeler and Levine, 1967;Wheeler and Smith, 1968), in connection with their theory of behavioral contagion. According to this theory, when an individual is instigated to make a response but fails to make it because of inhibitions arising within the situation, he may become disinhibited by observing a similarly motivated person carry out the same response.…”
Section: Justification For Observed Aggressionmentioning
confidence: 58%